Patterns of emotional and behavioural challenges in children living with HIV: results from a hyperendemic South African setting. Issue 3 (3rd July 2021) - Pillay, Kusturi; Tomita, Andrew; Paruk, Saeeda
ABSTRACT: This study examined the patterns of emotional and behavioural problems in children from an HIV hyperendemic sub-Saharan Africa setting. A cross-sectional questionnaire survey was administered to 198 parents/caregivers of children living with HIV aged 2–12 years, attending a paediatric HIV out-patient service at a public sector hospital in KwaZulu-Natal Province, South Africa. The parent version of the Strengths and Difficulties Questionnaire (SDQ) which consists of five sub-scales (i.e. emotional difficulties, conduct problems, hyperactivity/inattention symptoms, peer problems and prosocial behaviours) were used to capture data on emotional and behavioural problems in children. The results indicated that over half of sampled children (n = 115, 58.1%) had abnormal levels of problems in at least one sub-scale, with adjusted regression indicating that academic difficulties and delayed milestones were significantly associated (i.e. greater total SDQ score as a continuous measure). Lower parental/caregiver educational attainment (i.e. not having tertiary education) was the only parent/caregiver characteristic associated with greater emotional and behavioural problems. Given the high prevalence of emotional and behavioural problems and its link to academic difficulties and delayed milestones, the need for screening and developmental support for children living with HIV may be warranted.